Triptolide inhibits the growth of osteosarcoma by regulating microRNA-181a via targeting PTEN gene in vivo and vitro - Chunming Jiang; Xiang Fang; Hongxu Zhang; Xuepeng Wang; Maoqiang Li; Wu Jiang; Fei Tian; Liulong Zhu; Zhenyu Bian (Tumor Biology)
We aimed to study the anti-tumor effects of triptolide on osteosarcoma and the related molecular mechanisms. The cell viability, apoptosis portion, tumor size, tumor weight, and invasion of osteosarcoma cells were determined. The relative level of microRNA-181 in osteosarcoma tissues and the adjacent tissues was determined by quantitative real-time reverse transcription polymerase chain reaction. The target gene of microRNA-181a was determined and verified by luciferase report assay. At last, osteosarcoma cells were treated with triptolide and triptolide + microRNA-181a mimics to verify the relationship between triptolide and microRNA-181a. Triptolide inhibited the cell viability, promoted the apoptosis, decreased the tumor size and weight, and reduced the invasion of osteosarcoma cells. The level of microRNA-181a in osteosarcoma cells decreased significantly after treating with triptolide, and the relative level of microRNA-181a in osteosarcoma tissues was markedly higher than that in the adjacent tissues. PTEN was reported and verified the direct target gene of microRNA-181a. The overexpression of microRNA-181a decreased the inhibition of triptolide on osteosarcoma proliferation and promotion on osteosarcoma apoptosis. In conclusion, triptolide inhibited cell growth and invasion of osteosarcoma by regulating microRNA-181a via targeting PTEN gene in vivo and vitro.